Supporting carbon taxes: The role of fairness - Stephan Sommer; Linus Mattauch; Michael Pahle (RWI - Leibniz-Institut für Wirtschaftsforschung, 2020)
We conduct a discrete choice experiment with a sample of 6,000 German household heads to examine how fairness preferences influence the support for carbon taxes and revenue-recycling options. While it is well-known that carbon taxes are effective in reducing emissions and can be made progressive, they remain fairly unpopular with German citizens. Consequently, best practice to build public support for them remains a relevant question for which there is no consensus. We obtain two major results: First, while green spending is more popular in general, it is significantly more popular among those who are pro-environment and trust the government. Second, when restricted to options for direct revenue redistribution, Germans prefer lump-sum payments over directing payments to the poorest or the most affected. Importantly, choices over these options depend both on genuinely different conceptions of fairness and respondents' economic circumstances. Our findings have implications for building support for effective climate change mitigation policies with those who are not yet convinced. – – Wenngleich die ökonomischen Argumente für die Einführung einer CO2-Bepreisung überzeugend sind, ist die öffentliche Unterstützung dafür gering. Mittels eines Discrete-Choice Experimentes und einer Stichprobe von 6.000 deutschen Haushaltsvorständen untersuchen wir in diesem Artikel, wie Fairnesspräferenzen die Unterstützung für eine CO2-Bepreisung bei unterschiedlicher Verwendung der Einnahmen beeinflussen. Wir finden, dass jene Befragte, die die Einnahmen für die Förderung erneuerbarer Energie- und Verkehrsinfrastruktur verwenden möchten, eine CO2-Bepreisung eher unterstützen. Deren Unterstützung sinkt allerdings besonders stark bei höheren Steuersätzen, im Gegensatz zu Befragten, die eine Rückzahlung für einkommensschwache Haushalte befürworten. Betrachten wir ausschließlich direkte Formen der Umverteilung der Einnahmen an die Bevölkerung, zeigt sich, dass die Befragten Pro-Kopf-Zahlungen gegenüber Zahlungen an die Ärmsten oder am stärksten Betroffenen bevorzugen. Unsere Ergebnisse haben Auswirkungen auf die Akzeptanz einer CO2-Bepreisung, da die Unterstützung für diese wesentlich erhöht werden kann, wenn sie nach den Fairnesspräferenzen der Bürger gestaltet wird.
Keywords: A13; H23; Q54; 330; carbon pricing; climate change mitigation; fairness; redistribution; environmental tax reform